Measurement instrument for lean manufacturing - Nawanir, Gusman; Lim, Kong Teong; Othman, Siti Norezam (Center for Promoting Ideas, USA, 2015)
The present paper is aimed to provide a comprehensive measurement instrument for lean manufacturing, because there is no single agreement on how to measure the level of implementation of lean manufacturing.The measurement instrument has been generated in the present study based through an extensive literature review.The instrument has been tested for validity and reliability by using 49 samples of large and discrete part industries in Indonesia. It was concluded that the measurement items are valid and reliable.